Inhibition of RNF182 mediated by Bap promotes non-small cell lung cancer progression - Liu, Yating; Ouyang, Lianlian; Mao, Chao; Chen, Yuanbing; Liu, Na; Chen, Ling; Shi, Ying; Xiao, Desheng; Liu, Shuang; Tao, Yongguang (Frontiers in Oncology, 2023)
Ubiquitylation that mediated by ubiquitin ligases plays multiple roles not only in proteasome-mediated protein degradation but also in various cellular process including DNA repair, signal transduction and endocytosis. RING finger (RNF) proteins form the majority of these ubiquitin ligases. Recent studies have demonstrated the important roles of RNF finger proteins in tumorigenesis and tumor progression. Benzo[a]pyrene (BaP) is one of the most common environmental carcinogens causing lung cancer. The molecular mechanism of Bap carcinogenesis remains elusive. Considering the critical roles of RNF proteins in tumorigenesis and tumor progression, we speculate on whether Bap regulates RNF proteins resulting in carcinogenesis. Here we reported that the carcinogen Bap suppresses the expression of ring finger protein 182 (RNF182) in non-small cell lung cancer (NSCLC) cells, which is mediated by abnormal hypermethylation in an AhR independent way and transcriptional regulation in an AhR dependent way. Furthermore, RNF182 exhibits low expression and hypermethylation in tumor tissues. RNF182 also significantly suppresses cell proliferation and induces cell cycle arrest in NSCLC cell lines. These results demonstrated that Bap inhibits RNF182 expression to promote lung cancer tumorigenesis through activating AhR and promoting abnormal methylation.